Neuronal activity-dependent ATP enhances the pro-growth effect of repair Schwann cell extracellular vesicles by increasing their miRNA-21 loading - Saquel, Cristian; Catalan, Romina J.; Lopez-Leal, Rodrigo; Ramirez, Ramon A.; Necuñir, David; Wyneken, Ursula; Lamaze, Christophe; Court, Felipe A. (Frontiers in Cellular Neuroscience, 2022)
Functional recovery after peripheral nerve injuries is critically dependent on axonal regeneration. Several autonomous and non-cell autonomous processes regulate axonal regeneration, including activation of a growth-associated transcriptional program in neurons and the reprogramming of differentiated Schwann cells (dSC) into repair SCs (rSC), triggering the secretion of neurotrophic factors and the activation of an inflammatory response. Repair Schwann cells also release pro-regenerative extracellular vesicles (EVs), but is still unknown whether EV secretion is regulated non-cell autonomously by the regenerating neuron. Interestingly, it has been described that nerve activity enhance axonal regeneration by increasing the secretion of neurotrophic factors by rSC, but whether this activity modulates pro-regenerative extracellular vesicle (EV) secretion by rSC has not yet been explored. Here, we demonstrate that neuronal activity enhances the release of rSC-derived EVs and their transfer to neurons. This effect is mediated by activation of P2Y receptors in SCs after activity-dependent ATP release from sensory neurons. Importantly, activation of P2Y in rSCs also increases the amount of miRNA-21 present in rSC-EVs. Taken together, our results demonstrate that neuron to glia communication by ATP-P2Y signaling regulates the content of SC-derived EVs and their transfer to axons, modulating axonal elongation in a non-cell autonomous manner.